Penggunaan Data SPT dalam Penentuan Potensi Likuifaksi di Kota Solok - Atikah Harliz; Dyah Pratiwi Kusumastuti (Jurnal Sipil Krisna, 2023)
The area of West Sumatra which is at the confluence of 2 tectonic plates and 2 faults makes the area prone to earthquakes. One of the cities that has experienced an earthquake is Solok. One of the impacts of earthquakes is liquefaction events, namely the loss of strength of the sand layer due to increased pore water pressure. So that in planning construction in Solok it is necessary to review the potential for liquefaction in order to reduce construction damage and prevent liquefaction. To find out the potential for liquefaction as expressed by the value of the safety factor, it can be analyzed using standard penetration test data, namely N-SPT. The safety factor used in this study is the probability of 500 years and 2500 years. The results of the analysis of the safety factor obtained show that at each depth of the soil layer under review it has a value of < 1 so that the potential for liquefaction is quite high. The lowest safety factor is obtained at a depth of 4 – 6 m for a 500 year probability and 6 -7 m for a 2500 year probability which ranges from 0,12 – 0,16.